Red blood cell distribution width independently predicts medium-term mortality and major adverse cardiac events after an acute coronary syndrome - Turcato, Gianni (Ann Transl Med, 2016)
BACKGROUND: The value of red blood cell distribution width (RDW), a simple and inexpensive measure of anisocytosis, has been associated with the outcome of many human chronic disorders. Therefore, this retrospective study was aimed to investigate whether RDW may be associated with medium-term mortality and major adverse cardiac events (MACE) after an acute coronary syndrome (ACS). METHODS: A total number of 979 patients diagnosed with ACS were enrolled from June 2014 to November 2014, and followed-up until June 2015. RESULTS: The RDW value in patients with 3-month MACE and in those who died was significantly higher than that of patients without 3-month MACE (13.3% vs. 14.0%; P<0.001) and those who were still alive at the end of follow-up (13.4% vs. 14.4%; P<0.001). In univariate analysis, RDW was found to be associated with 3-month MACE [odds ratio (OR), 1.70; 95% CI, 1.44–2.00, P<0.001]. In multivariate analysis, RDW remained independently associated with 3-month MACE (adjusted OR, 1.36; 95% CI, 1.19–1.55; P<0.001) and death (adjusted OR, 1.34; 95% CI, 1.05–1.71; P=0.020). The accuracy of RDW for predicting 3-month MACE was 0.67 (95% CI, 0.66–0.72; P<0.001). The most efficient discriminatory RDW value was 14.8%, which was associated with 3.8 (95% CI, 2.6–5.7; P<0.001) higher risk of 3-month MACE. Patients with RDW >14.8% exhibited a significantly short survival than those with RDW ≤14.8% (331 vs. 465 days; P<0.001). CONCLUSIONS: The results of this study confirm that RDW may be a valuable, easy and inexpensive parameter for stratifying the medium-term risk in patients with ACS.